Development of Improved Trip Attraction Rates for Small and Medium-Sized Travel Demand Models. Issue 1 (2016) - Sperry, Benjamin R.; Chigoy, Byron T.; Green, Lisa K.; Hard, Ed
Accurate data are essential for the development of robust and valid travel demand models to support the planning activities of metropolitan planning organizations (MPOs). The Travel Survey Program of the Texas Department of Transportation (DOT) includes workplace travel surveys to develop trip attraction rates for travel demand modeling activities. This paper reports the findings of a research study that developed a comprehensive database of workplace travel surveys conducted by the Texas DOT over the past 13 years. The final master database contained data from more than 63, 000 trips at more than 5, 100 establishments across 15 urban areas in Texas. Trip attraction rates for three trip purposes (home-based work, home-based nonwork, and non-home based) were calculated from these data, with segmentation according to establishment type, urban area size, and the population density of the traffic analysis zone in which the establishment was located. Trip attraction rates were calculated for person trips and auto trips. One of the key findings from this study was that the trip attraction rates varied across area types and indicated that population density contributed to the trip attraction characteristics of workplace establishments. The findings of this research can be used by MPOs of all sizes—especially those serving small and medium-sized urban areas—to improve travel demand models by providing more improved trip attraction rates for a variety of contexts.